Tailored Catalytic Nanoframes from Metal–Organic Frameworks by Anisotropic Surface Modification and Etching for the Hydrogen Evolution Reaction. Issue 9 (15th January 2021) - Cai, Ze‐Xing; Wang, Zhong‐Li; Xia, Yan‐Jie; Lim, Hyunsoo; Zhou, Wei; Taniguchi, Ayano; Ohtani, Masataka; Kobiro, Kazuya; Fujita, Takeshi; Yamauchi, Yusuke
Abstract: A facile anisotropic surface modification and etching strategy is presented for the synthesis of hollow structured ZIF‐67 nanoframes. The strategy uses structural and compositional distinctions between each crystallographic facet of truncated rhombic dodecahedrons ZIF‐67 (tZIF‐67 RDs) and the moderate coordinating and etching effects of cyanuric acid (CA). The CA can anisotropically modify and protect the 110 facets from etching, causing the six 100 facets be selectively etched via an inside‐out manner, and finally forming the hollow nanoframes. The surface‐modified hollow tZIF‐67 RDs can be facet‐selectively etched by metal salts in an outside‐in manner to give metal‐doped tZIF‐67 nanoframes. After calcination, the metal‐tZIF‐67 hybrids are converted into metal‐Co alloy/C composite catalysts with hollow nanoframed structures. The PtCo/C catalyst with only 5.9 wt % Pt exhibits high catalytic activities and stabilities in the hydrogen evolution reaction (HER) in acidic solutions. Abstract : CA molecules can anisotropically modify and protect the 110 facets of the tZIF‐67 crystal from etching, causing the six 100 facets be selectively etched via an inside‐out manner, and finally forming the hollow nanoframes. The surface modified hollow tZIF‐67 can further be facet‐selectively etched by metal salts in an outside‐in manner to give metal‐doped tZIF‐67 nanoframes.